2018
DOI: 10.1016/j.physb.2017.10.123
|View full text |Cite
|
Sign up to set email alerts
|

Electrical switching and oscillations in vanadium dioxide

Abstract: We have studied electrical switching with S-shaped I-V characteristics in two-terminal MOM devices based on vanadium dioxide thin films. The switching effect is associated with the metal-insulator phase transition. Relaxation oscillations are observed in circuits with VO2-based switches. Dependences of the oscillator critical frequency Fmax, threshold power and voltage, as well as the time of current rise, on the switching structure size are obtained by numerical simulation. The empirical dependence of the thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 20 publications
0
29
0
2
Order By: Relevance
“…The jump in resistance between these phases can reach several orders of magnitude (10-10 4 ), depending on the structure of the film [55]. Many researchers, including us [56], have demonstrated that the effect of electrical switching occurs due to MIT, when the current passing through the VO 2 structure heats it with Joule heat to a temperature T t . There is a strong dependence of the threshold switching parameters on the ambient temperature T 0 [46].…”
Section: Discussionmentioning
confidence: 99%
“…The jump in resistance between these phases can reach several orders of magnitude (10-10 4 ), depending on the structure of the film [55]. Many researchers, including us [56], have demonstrated that the effect of electrical switching occurs due to MIT, when the current passing through the VO 2 structure heats it with Joule heat to a temperature T t . There is a strong dependence of the threshold switching parameters on the ambient temperature T 0 [46].…”
Section: Discussionmentioning
confidence: 99%
“…One of the technological problems of miniaturization of oscillator circuits is the application of capacitors that occupy a large area of the crystal using standard CMOS technology. For example, with an inter-electrode dielectric thickness of 10 nm, the specific capacitance of the capacitor is ~ 3 fF / μm 2 , and the capacitances with a nominal value of more than 1 pF are needed to generate oscillations on submicron-sized switches [16]. When implementing the capacitor model of the oscillator, nearly 330 μm 2 of the crystal area is required to manufacture the capacitor, while only ~ 1 μm 2 is used to manufacture the switch and the load or current resistors.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, for the manufacturing of artificial neurons, we propose to use elements with a stable S-shaped I -V characteristic, such as switches based on transition metal oxides with a metal-insulator transition [25][26][27]. Implementations of neuron models on the VO 2 switch are described in References [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%